"I don't believe it." Acceptance and skepticism of genetic health information among African-American and White smokers. (July 2017) - Waters, Erika A.; Ball, Linda; Gehlert, Sarah
Abstract: Rationale: Effective translation of genomics research into practice depends on public acceptance of genomics-related health information. Objective: To explore how smokers come to accept or reject information about the relationship between genetics and nicotine addiction. Methods: Thirteen focus groups ( N  = 84) were stratified by education (seven < Bachelor's degree, six ≥ Bachelor's degree) and race (eight black, five white). Participants viewed a 1-min video describing the discovery of a genetic variant associated with increased risk of nicotine addiction and lung cancer. Next, they provided their opinions about the information. Two coders analyzed the data using grounded theory. Results: Pre-video knowledge about why people smoke cigarettes and what genetic risk means informed beliefs about the relationship between genes and addiction. These beliefs were not always consistent with biomedical explanations, but formed the context through which participants processed the video's information. This, in turn, led to information acceptance or skepticism. Participants explained their reactions in terms of the scientific merits of the research and used their existing knowledge and beliefs to explain their acceptance of or skepticism about the information. Conclusion: Laypeople hold complex understandings of genetics and addiction. However, when lay and biomedical explanations diverge, genetics-related health information may be rejected. Highlights: Lay conceptualizations of genetic risk include a complex constellation of beliefs. Lay skepticism of genetic information can result from divergent lay/expert beliefs. Genetic communications that incorporate lay beliefs may be more effective.